2015
DOI: 10.1186/s12978-015-0102-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of skilled assistance seeking behavior to pregnancy complications among women at southwest Ethiopia: a cross-sectional community based study

Abstract: BackgroundIn Ethiopia, about 20,000 women die each year from complications of pregnancy and child birth with many more maternal morbidities occurring for each maternal deaths. This makes Ethiopia one of the highest countries for maternal deaths in the developing world. This study attempted to assess women’s skilled assistance seeking behaviour for pregnancy complications among those who gave birth.MethodA cross-sectional community based study was conducted among women who gave birth within one year regardless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 10 publications
6
21
1
Order By: Relevance
“…Studies which identified demand-side affordability as a barrier reported primarily on household resources and willingness to pay rather than cash flow within society [22, 23, 25, 26, 31, 32, 34, 3638, 40, 41, 4648, 50, 52, 61, 66–71, 7375, 78, 79, 83, 85112]. Some studies cited reports by pregnant women of being too busy or having no time as reasons for non-use of maternity care services [22, 26, 63, 86, 100, 113, 114], which represent opportunity costs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies which identified demand-side affordability as a barrier reported primarily on household resources and willingness to pay rather than cash flow within society [22, 23, 25, 26, 31, 32, 34, 3638, 40, 41, 4648, 50, 52, 61, 66–71, 7375, 78, 79, 83, 85112]. Some studies cited reports by pregnant women of being too busy or having no time as reasons for non-use of maternity care services [22, 26, 63, 86, 100, 113, 114], which represent opportunity costs.…”
Section: Resultsmentioning
confidence: 99%
“…Household expectations included service users’ minimal expectations of cleanliness and non-interference during labour and delivery at health facilities, ability to meet cultural expectations [30] and a perception that health workers were too busy [91]. Social problems related to women’s low self-esteem and assertiveness were highly reported and manifested in various forms such as the husband’s denial of permission, the need for the husband’s/relative’s permission, women’s low decision-making power/autonomy [22, 23, 27–29, 33, 39, 46, 49, 51, 60, 62, 64, 66, 68, 69, 71, 73, 78–80, 94, 97, 104, 110, 111, 114122] and delayed/ineffective decision-making within the family [47, 56, 65, 123, 124]. Shyness, fear or shame were also reported [28, 113], particularly among sub-groups like teenagers who were possibly afraid of being reprimanded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies that examined factors associated with care seeking found that women belonging to wealthier households were more likely to seek skilled care for antepartum complications [11, 13]. Factors associated with skilled birth attendants during intrapartum period included mothers’ occupation, higher parity, complications during antepartum period, having antenatal care [14], and closer distance to a health facility [13, 15, 16]. In addition, access to skilled attendants, availability of quality care and associated medical cost remained major barriers to seeking care [11].…”
Section: Introductionmentioning
confidence: 99%
“…Most intercurrences can lead to serious complications and the best way to avoid such complications is through an appropriate and qualified health care [8]. Some studies have identified factors and behaviors that can minimize the effects of pregnancy complications, such as increased educational level, ease of access to the health facility, the availability of the transport system, family support, experience of a previous pregnancy, favorable economic conditions and qualified health care [9,10] In fact, one highlights the importance of ensuring those users a qualified prenatal care, since, through that service, health professionals can perform the monitoring of the main pregnancy complications seeking to avoid major complications for mother and child [2].…”
Section: Discussionmentioning
confidence: 99%